Kadar CRP pada Pasien Tuberkulosis Paru dengan Terapi Obat Anti Tuberkulosis di Puskesmas Oebobo Kota Kupang - Ni Ketut Yuliana Sari; Agnes Rantesalu; Kuntum Ekawati Nurdin (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Tuberculosis (TB) is one of the top 10 causes of death worldwide. Anti-tuberculosis drugs (OAT) are the most important component of TB treatment. CRP can be used as a marker of tuberculosis activity and severity and can predict the course of the disease. This study aimed to determine CRP levels in TB patients at the Oebobo Community Health Centre in Kupang City as a monitor of response to TB treatment. The research design was observational analytic using a cross sectional approach by measuring CRP levels in the form of high sensitivity CRP in pulmonary TB patients with OAT therapy. The results showed that of the 27 respondents (20 men, 7 women), 18 people (66.66%) had CRP ≤ 10 mg/L and 9 people (33.33%) had CRP > 10 mg/L. Based on the length of treatment, CRP levels > 10.0 mg/L were most prevalent in respondents who were undergoing intensive treatment, namely 6 people (22.22%). Respondents with advanced treatment had more CRP levels ≤ 10.0 mg/L (26.63%) than > 10.0 mg/L (11.11%).